2005
DOI: 10.1177/1069072704270272
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Big Five Personality Traits and Career Decidedness Among Early and Middle Adolescents

Abstract: Big Five personality traits were analyzed in relation to career decidedness among adolescents in middle and high school. Participants were 248 7th-grade, 321 10thgrade, and 282 12th-grade students. As hypothesized, Conscientiousness was positively and significantly correlated with career decidedness in all three grades. Openness and Agreeableness were found to be positively related to career decidedness for these middle and high school students. Emotional Stability was positively, significantly related to care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
70
4
11

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(103 citation statements)
references
References 63 publications
(66 reference statements)
18
70
4
11
Order By: Relevance
“…Moreover, it was found that neuroticism was positively related with impetuous indecisiveness. This is a consistent finding with the findings from the previous studies (e.g., Kelly & Shin, 2009;Lounsbury et al, 2005;Page et al, 2008). Also, this finding shows that neuroticism has a role in impetuous indecisiveness.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, it was found that neuroticism was positively related with impetuous indecisiveness. This is a consistent finding with the findings from the previous studies (e.g., Kelly & Shin, 2009;Lounsbury et al, 2005;Page et al, 2008). Also, this finding shows that neuroticism has a role in impetuous indecisiveness.…”
Section: Resultssupporting
confidence: 93%
“…In other words, individuals who effectively communicate with others have a low level of exploratory indecisiveness. Also, it can be expected that individuals who are sociable, friendly, alive and talkative in their decision making approach have lower levels of exploratory indecisiveness (Lounsbury, Hutchens, & Loveland, 2005). Indeed, findings obtained by Gati et al (2011) support this finding.…”
Section: Resultsmentioning
confidence: 76%
“…The most common theoretical frameworks involving these sub-types have been personality led, e.g. trait based anxiety, self-esteem, locus of control, emotional stability, neuroticism (see Gordon 1998;Hirschi 2011;Lounsbury, Hutchens and Loveland 2005). For example, Lounsbury et al (1999;Lounsbury, Hutchens and Loveland 2005) studied the personality antecedents of career decidedness in relation to college students, finding positive correlations with traits such as student conscientiousness and agreeableness, but negative relationships with neuroticism (Lounsbury et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…To assess decidedness, the Career Decidedness Scale (John W Lounsbury, Tatum John W Lounsbury, Hutchens, & Loveland, 2005) and has been widely used in employment studies (Earl & Bright, 2007;Feldt & Woelfel, 2009;Uthayakumar, Schimmack, Hartung, & Rogers, 2010). In terms of reliability, Cronbach's alpha was used and scored 0.751.…”
Section: Decidednessmentioning
confidence: 99%